Education of Primary Class Students in Spiritual and Moral Spirit Issues - Sabokhat USMANOVA (Euro Asian Journal Publishing, 2024)
In the Republic of Uzbekistan, the education reform is aimed at improving the morale of individual personnel, improving modern teaching and upbringing methods. As a point of view, both the class and the moral and ethical qualities educate the staff to solve the problem described in the article is the movement for help
Keywords: Ethical education; skills development-compliance; formation of ethical personnel